Excellent electrochemical properties of Ni-rich LiNi0.88Co0.09Al0.03O2 cathode materials co-modified with Mg-doping and LiBO2-coating for lithium ion batteries. (17th January 2023) - Guo, Mi; Luo, Liang; Chen, Shulin; Wang, Zhenzhen; Zuo, Pengjian; Wang, Zhenbo
Abstract : The cycle life of LiNi0.88 Co0.09 Al0.03 O2 was considerably improved by co-modification with Mg-doping and LiBO2 -coating. Abstract : Although LiNi0.88 Co0.09 Al0.03 O2 with high Ni content has received extensive attention as an inexpensive cathode material possessing high energy density, it also encounters poor cycling issues because of the micro-cracks caused by phase transition and serious side reactions between the electrodes and the electrolyte. In this study, dual-modification of the material is achieved by LiBO2 -coating and Mg-doping, aiming to stabilize its crystal structure and reduce its surface activity. Furthermore, a systematic exploration was made into the influence of Mg-doping and LiBO2 -coating layers on the particle morphology, crystal structure and electrochemical traits. According to the XRD (X-ray diffraction) outcomes, Mg-doping and LiBO2 -coating both expand the interplanar space and lower the Ni 2+ /Li + cation mixing. According to the TEM (transmission electron microscopy) and XPS (X-ray photoelectron spectroscopy) findings, the LiBO2 -coating layer is within 25 nm and the Mg-doping heightens the Ni 2+ content. In the meanwhile, the electrochemical measurement indicates that dual-modification with LiBO2 -coating and Mg-doping was effective in strengthening the discharge ability, rate capability and cycling behavior of LiNi0.88 Co0.09 Al0.03 O2 due to the elevated rate of Li + diffusion, the constrained electrode side reaction with the electrolyte, and the improved reversibility of the H2 to H3 phase. Besides, the cylindrical 18650 battery with the co-modification cathode show excellent prolonged cycling stability both at room and high temperature.